Perbandingan Kombinasi Senam Kaki dengan Hidroterapi dan Tanpa Hidroterapi Terhadap Range Of Motion Aktif Ekstremitas Bawah pada Lansia - Fahrezi, Andhwika Afif; Supatmo, Yuswo; Marijo, Marijo; Adji, Raden Mas Soerjo (RSUP Dr. Kariadi, 2023)
Background: Aging results in a decrease in various body functions, one of them is in the aspect of mobility. Increasing age can reduce the range of motion of the joints. One of the easy physical activities for the elderly is foot exercise and hydrotherapy (warm water soaks) in order to minimize the decrease in ROM. Aim : To compare the combination of foot exercises with hydrotherapy and without hydrotherapy on active ROM of the lower extremities in the elderly. Methods : This research is an experimental study with parallel 3 groups pre and post-test design. The research subjects were 21 elderly people in RW 04 Karang Wetan, West Ungaran, Semarang Regency. Active ROM of the lower extremity was measured before and after intervention using a goniometer. analyzing the data of this study using the Paired T test and One Way ANOVA method. Results: There was no significant increase in the active ROM of the lower extremities in the control group, p=0.114 (p>0.05). The range of active motion of the lower extremities (pre test to post test) in the combination treatment group of foot exercise and hydrotherapy p < 0.001 (p < 0.05) and the treatment group of foot exercise p = 0.001 (p < 0.05) experienced a significant increase . However, there was no significant difference in the increase in active ROM of the lower extremities in the combination treatment group with foot exercises and hydrotherapy, p=1.00 (p<0.05) and the foot exercise treatment group. Conclusion:Physical activity in the form of a combination of foot exercises with hydrotherapy and without hydrotherapy performed 3 times a week for 5 weeks has been shown to increase the active ROM of the lower extremities in the elderly. However, there was no significant difference between the two which was more effective in increasing the active ROM of the lower extremities in the elderly.